The Impact of Quantum Learning in Secondary School Students: A Case Study in Geometry - Alhaitami, Akhmad (Journal of Mathematical Pedagogy (JoMP), 2020)
This research was aimed to produce learning device at Quantum Teaching which focused on geometry and to know effectiveness of Quantum teaching on Geometry in grade X. The development of learning device was used 4-D model (Thiagarajan, et al.) with several modifications. The learning device which had been gained were Lesson Plan, Students Worksheet, and Test Instruments. The data source of this study was the students at Madrasah Aliyah Negeri (MAN) 5 Barabai grade X in academic year 2014/2015: X-A would be the trial class and X-B would be the implementative class. Based on the trial result, which had been obtained was a good instruments of quantum teachings after it was being validated by experts and it had fulfilled these requirements: (1) teachers ability to manage this learning was good, (2) students activities were in ideal time, (3) students responses was positive, and (4) Test instruments was valid, reliable and sensitive. Thus, based on descriptive analysis, this quantum learning was also effective to learn geometry because it had fulfilled the effectiveness requirements, which are: (1) teachers ability to manage this learning was good, (2) students activities were in ideal time, (3) students responses were positive, and (4) classically, students reached their mastery standard: there were 83,33% from all of the students who got â‰¥70 for their score.Keywords: The Development of Learning Device, Effectiveness of Quantum Teaching, Geometry.